Ultrasound pretreatment and solvent extraction parameters effects on the nutritional characteristics of Indonesian shortfin eel (Anguilla bicolor bicolor) protein concentrate - Kumoro, Andri Cahyo; Wardhani, Dyah Hesti; Kusworo, Tutuk Djoko; Djaeni, Mohamad; Azis, Yusuf Ma'rifat Fajar; Alhanif, Misbahudin; Ping, Tan Chin (Elsevier, 2025)
Protein concentrate (PC) is a potential solution to address the global protein shortage, with Indonesian shortfin eel being a suitable raw material. This research investigates the impact of ultrasound pretreatment and extraction parameters on the nutritional quality of eel protein concentrate (EPC). The study involved ultrasonic pretreatment at different times and power, and solvent extraction with different solvents, temperature, and solvent-solid-feed-ratio (SSFR). The results showed that the recommended conditions for EPC preparation were a mixture of ethanol-hexane, ultrasonic pretreatment at 250 W for 25 min, extraction temperature and SSFR of 40 °C and 6:1 v/w. The protein content of EPC increased gradually with the increase of SSFR until it reached a ratio of 6:1, further increase in SSFR promoted the development of a pseudo-homogeneous system, leading to a reduction in the solvent-eel flesh contact and the relative velocity between the extracting solvent and eel flesh, and consequently decreased the extraction yield. The prepared EPC is classified as type B EPC, with a protein content of 89.62 %w.b. and a lipid content of 2.21 %w.b. The EPC contains five types of peptides with a molecular weight of 5.00–76.00 kDa, with the main fraction having a MW ranging from 10.00 to 15.00 kDa, indicating potential for functional food products.